Approaches towards the synthesis of saxitoxin alkaloids - Pearson, Aaron Daniel, author; Williams, Robert M., advisor; Wood, John L., committee member; Kennan, Alan J., committee member; Fisher, Ellen R., committee member; Woody, Robert W., committee member (Colorado State University. Libraries, 2013)
Zetekitoxin AB is a toxin isolated from the Panamanian golden frog (Atelopus zeteki). The structure and activity of zetekitoxin AB was a mystery for 30 years until 2004 when it was elucidated by Yamashita and coworkers. It was found to be a potent analog of Saxitoxin, a marine neurotoxin. Saxitoxin is a sodium channel blocker and has been used extensively as a research probe. Zetekitoxin AB shows an affinity profile similar to saxitoxin, but is considerably more potent. Due to the endangerment of the Panamanian golden frog there is no source of zetekitoxin AB, preventing further studies. Presented herein is a concise synthesis of 4,5-epi-11-hydroxy-saxitoxinol, which utilizes D-ribose to direct an asymmetric Mannich reaction. This approach allows many modes of reactivity, which can be used to potentially access various analogs of saxitoxin with novel bioactivity.
Keywords: zetekitoxin AB; saxitoxin; diamino acid; gonyautoxin 3; Mannich reaction